Durga-Mahisasuramardini - Temples of India Project Team (Jio Institute, 2024)
This image of Durga-Mahisasuramardini in active worship is smeared with black paint and clothed, which obscures the details of the image. It is one of the many images, contemporaneous to the Harsha shrine, affixed in the enclosure of the Bhairon shrine.